Trading Profits in Dutch Auction Self-Tender Offers. - Kadapakkam, Palani-Rajan; Seth, Sarabjeet (Journal of Finance, 1994)
The authors document abnormal trading profits in Dutch auction self-tenders. Tender period profits–buying after announcement and selling just before expiration–are 1.74 percent. Buying just before expiration and tendering yields abnormal profits of 1.36 percent. Total profits from buying just after announcement and tendering remain positive after adjusting for bid-ask spreads. Trading profits are higher for smaller firms and positively correlated with tender period unsystematic risk, suggesting that they arise due to the pricing of event risk.